The monogamy gap men, love, and the reality of cheating - Anderson, Eric, 1968- (Oxford ; New York : Oxford University Press, 2012)
'The Monogamy Gap' is a groundbreaking volume that explains why men cheat. Drawing on a range of theories across academic disciplines, the book highlights the biological compulsion of the sexual urge, the social construction of the monogamous ideal, and the devastating chasm that lies between them.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Men -- Sexual behavior; Monogamous relationships; Sex; Love